Internet share of advertising expenditure: growth drivers and inhibitors in the Brazilian market - Pita, Guilherme Szyszko (2011)
Internet advertising spending as a percentage of total advertising expenditure varies significantly from one country to another. The figure is as low as 4.7% in the Brazilian market and as high as 28.5% in the British market (ZenithOptimedia, 2011b). A few reasons explain such disparity. At the macro level, Internet share of advertising spending is strongly connected to variables such as gross domestic product per capita and Internet penetration within the population. At the micro level, qualitative research has been done to identify drivers and inhibitors of Internet share of advertising spending growth in the Brazilian market. The vast list of inhibitors appears to have deeper impact on how market professionals make decisions of advertising investment allocation per media type. Due to regulation, self-policing and industry dynamics, much of the decision-making authority is performed by advertising agencies. These appear to have strong economic incentives to select other media types than Internet when defining media plans. At the same time, regulation and self-policing provide disincentives for companies known as media brokers to operate in the local market. The lack of qualified professionals and the limited standardization also play important roles to inhibit a higher Internet share of advertising spending in Brazil. The convergence of the quantitative results with the qualitative findings indicates possible outcomes to why Internet share of advertising spending in Brazil is so low. Firstly, the share is explained by the development stage of countries. The richer and the more developed a country is, the higher the Internet share of advertising spending tends to be. Secondly, the economic emerging stage of Brazil potentially gives room to the raising of market inefficiencies such as disproportionate rebate programs offered to key decision makers of media budget allocation. This fact apparently produces a negative feedback, contributing to keep the Internet share of advertising spending low in the overall advertising spending.